Fuzzy Logic And IOT Based Air Humidity Control System For Orchid Plants. - Farisih, Moch Rizky; Misbah (Riwayat: Educational Journal of History & Humanities, 2023)
Air humidity is a measure of the content of water vapor in the form of gas in the air to produce water vapor such as fine dew around environments that have high temperatures. Meanwhile, orchid plants have different levels of temperature, humidity and temperature with other plants. Because generally good moisture for orchid plants ranges from 60 – 80%. Humidity should not be too high at night and not too low during the day. In addition to humidity, the temperature where you plant orchids must also be maintained. The ideal temperature for orchids is: daytime temperatures between 27-30 degrees Celsius and night temperatures between 21-24 degrees Celsius. It must be continuously controlled so that it can produce good quality orchids. When cultivating orchids, it is necessary to pay attention to the water that is not poured too much or too little, it can cause decay or drying out of the roots of the plants so that the plants can die quickly. Fuzzy logic control system that will be used to control air humidity. The actuators used in this study include relays, DC motor pumps, DC fans and lighting. For how the actuator works, a supporting component is needed, namely the nozzle functions to spout water smoothly for the watering process. During the watering process in the greenhouse, the sensor will detect a signal of decreasing soil moisture level so that the signal will be forwarded to Esp32. For the benefit of developing this research, it can help millennials who are interested in the field of cultivation regarding technological developments in orchid plants in modern greenhouses and lovers of ornamental plants are increasing .